A Narrative Review of the Recent 'Ice' Epidemic: An Australian Perspective. (April 2021) - Pisarski, Konrad
Background: The use of methamphetamine or amphetamine stimulant drugs has been identified by authoritative public health bodies as a global health issue, with a worrying trend towards production and consumption of a higher purity crystalline form methamphetamine (ice) over the past decade. This trend has been well documented within Australia, resulting in a public perception of there being an 'ice' epidemic in regional/rural areas. Considering the illicit nature of ice, monitoring it is challenging and as such little information is available regarding the actual extent of methamphetamine use, harms and patterns in regional/remote Australia. Aim: To collate the available literature regarding methamphetamine use in regional/rural Australia and identify gaps in the literature. Methods: A literature search was conducted by searching 6 databases (PUBMED, Medline, CINAHL, EMBASE, PsycINFO and SCOPUS) following which exclusion/inclusion criteria were applied. Included papers were appraised with the Joanna Briggs Institute Critical appraisal tools and synthesised in light of the sociocultural, ethnic and geographic differences in methamphetamine use in Australia. Results: Regarding rural/regional Australia there is a significant lack of research into methamphetamine use, patterns and epidemiology since the rise of crystalline methamphetamine in 2013. The existing literature available suggests great variability in methamphetamine harms in rural communities. This can be a double-edged sword however, as the introduction of ice into a remote/rural community may result in greater harms if it becomes ingrained in local customs. Similarly, there is a lack of research into the specific factors within Indigenous communities leading to an increased rate of methamphetamine use amongst members. Recommendation: Future research should address the causes of variance in methamphetamine harms in rural/remote regions. Although the scope of this paper was the Australian context, a wider international approach may yield useful information.